World Dance Day: A Cultural Conservation in Maintaining Local Wisdom of Traditional Arts - Ana Rosmiati; Supriyanto Supriyanto; Joko Budiwiyanto; Tubagus Mulyadi (Gelar : Jurnal Seni Budaya, 2022)
The research entitled " World Dance DAay: A Cultural Conservation in Maintaining Local Wisdom of Traditional Arts" was conducted to explore the strengths in maintaining the existence of traditional arts, which began to shift with the introduction of Western culture. World Dance Day was a dance event with a duration of 24 hours. This event had been going on for several years. It had become a routine agenda at ISI Surakarta by involving the public, community, art activists, cultural observers, foreign participants, and others. World Dance Day could be used as branding in building ISI Surakarta amid competition among higher education institutions. Organized events could be media promotions both domestically and internationally. This event was held once a year in April, on the 29th. The problem in this research was how to maintain the existence of traditional arts through the activation of World Dance Day and brand World Dance Day activation as a medium for introducing art. The purpose of the research was to find ways to maintain the existence of traditional arts through the World Dance Day activation and to find ways to make World Dance Day branding activation a medium for introducing dance arts to the community. This type of research was qualitative descriptive research. The data source in this study was primarily data source in the form of World Dance Day activation. The monitoring method was carried out by identifying the types of activation included in World Dance Day. Data were obtained from the World Dance Day activation. Researchers directly observed the World Dance Day activation and saw Youtube and other social media. The result of this research was to find ways to maintain the existence of traditional arts through World Dance Day activation. Apart from that, they also carried out branding in the form of World Dance Day activation as a medium for introducing dance arts to the community.